Mechanical Response and Failure Mechanisms of Block Caving Bottom Structures Under Dynamic Conditions Induced by Slope Rockfalls - Xinglong Feng; Guangquan Li; Zeyue Wang; Xiongpeng Zhu; Zhenggao Huang; Hang Lin (Applied Sciences)
The stability of bottom structures in block caving mines is significantly challenged by impact loads generated from large rockfalls and ore collapses on slopes. This study aims to investigate the mechanical response and failure characteristics of bottom structures under such dynamic and cyclic loading conditions. Discrete element methods (DEMs) were employed to simulate the impact load amplitudes caused by large rockfalls on bottom structures. Specimens with identical mechanical properties to the bottom structure were fabricated at a 1:100 scale, based on the principle of similarity ratio tests. Three distinct types of impact loads were identified and analyzed: overall impact from large-scale slope collapses, localized impact from partial rock and soil mass collapses, and continuous multiple impacts from progressive slope failures. True triaxial tests were conducted to evaluate the mechanical response of the bottom structure under these loading scenarios. The results indicate that while overall and multiple impact loads from slope collapses do not lead to catastrophic failure of the bottom structure, severe damage occurs under a 100 m thickness of ore and large block impacts. Specifically, the inner walls of ore accumulation troughs peel off, and ore pillars between troughs fracture and fail. This study highlights the need for advanced experimental and numerical approaches to accurately predict the stability and failure modes of bottom structures under complex loading conditions.